Cartoon Chronicles: Nurturing Oratory Skills in Junior High - Aristanty, Novi; Santoso, Dian Rahma (Universitas Muhammadiyah Sidoarjo, 2023)
This study aimed to assess the impact of utilizing cartoon movies as a learning medium in teaching monologue to enhance speaking abilities among junior high school students. Employing a pretest-treatment-posttest design within a pre-experimental study model, the research focused on a classroom using the cartoon movie